REFLECTION OF THE TIME: THE CONCEPT OF THE HISTORICAL NOVEL IN LITERATURE (Scientific journal of the Fergana State University, 2024)
This article is an analysis of the concept of the historical novel in literature with an emphasis on the reflection of time. The work examines the main aspects of the historical genre, its evolution and significance in modern literature. Particular attention is paid to the ways in which authors use time to create atmosphere, plot development, and character development in historical works. Various approaches to the interpretation of historical events are analyzed, as well as their influence on the formation of literary images.